9t-7=3t-5

Simple and best practice solution for 9t-7=3t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9t-7=3t-5 equation:


Simplifying
9t + -7 = 3t + -5

Reorder the terms:
-7 + 9t = 3t + -5

Reorder the terms:
-7 + 9t = -5 + 3t

Solving
-7 + 9t = -5 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
-7 + 9t + -3t = -5 + 3t + -3t

Combine like terms: 9t + -3t = 6t
-7 + 6t = -5 + 3t + -3t

Combine like terms: 3t + -3t = 0
-7 + 6t = -5 + 0
-7 + 6t = -5

Add '7' to each side of the equation.
-7 + 7 + 6t = -5 + 7

Combine like terms: -7 + 7 = 0
0 + 6t = -5 + 7
6t = -5 + 7

Combine like terms: -5 + 7 = 2
6t = 2

Divide each side by '6'.
t = 0.3333333333

Simplifying
t = 0.3333333333

See similar equations:

| 20y-6=18y+4 | | 4(6a+2)=-88 | | -2(3s-3)-6=-3(6s+0)-5 | | 3(-6t+4)=-5t+2(t-9) | | 14+b=13-3b | | 12x^4=2x^2+4 | | 2ysquare=12y-5y | | 4y+3=127 | | X^2-9y^2+6x-36y-36=0 | | 10=(6+9b)+7b | | 3log(2)=9log(x) | | x+6=4x-21 | | 6x+8+2x+4= | | 5.36-0.4m=26.8-0.4m | | 3(4x+3)+4x=61 | | (35-2x)(70-2x)= | | Y^2=2px+p^2 | | 13x+2=13x-4 | | (x-b)=x | | 2x-5/7=8/25 | | x+(-16)=-12 | | nx=3y-5 | | 2/3(m-8)=9 | | 35=3x+2(x-5) | | 24000/X=0 | | 0.2x-3.4=0.5x-2.5 | | 6=1-3p | | 130=24x+2 | | 18x-6=120 | | 6=1-3p+2 | | 5x-2=2(5x+1)-1 | | 3(18-2^3)/2 |

Equations solver categories